(untitled) (Fiep Bulletin - online, 2020)
In the context of cultural transformation engendered by the new technological society, the challenge facing the school institution in terms of reconfiguring its historically established practices is great. From the advent of the Internet and digital technologies, there are many possibilities for building knowledge and preparing citizens for active life. The way to build knowledge is collaborative. Participation and interaction in the global world permeated by these technologies must be the scope of this new school; and teachers are called to use virtual tools for the benefit of body education, which requires a fresh look at the body. The collaborative construction of knowledge, citizen participation and preparation for active life, as well as their critical formation, are in this agenda. And Physical Education, as a compulsory curricular component of Basic Education, which has its foundations in the concepts of body and movement, also needs to be sensitive to this theme, of great relevance to the current scenario. Through bibliographic research, this article aims to discuss these issues, dear to the educational area, in particular, to school Physical Education. Therefore, there is a discussion about the body place in the institutions of formal education, its relations with the initial formation in Physical Education and with the infamous STS curriculum. Topics of socio-scientific relevance can and should be approached by the area, aiming to develop values ??and attitudes for responsible decision making in the face of real situations, in the light of a thematic approach aimed at a problematizing, dialogical, reflective and argumentative education. reality, as in Paulo Freire, starting from reflections on basic contradictions existing in existential situations.